The Siege of Vicksburg : Climax of the Campaign to Open the Mississippi River, May 23-July 4, 1863 - Smith, Timothy B., 1974- (Book collections on Project MUSE., 2021)
"The capture of Vicksburg by the US Army was one of the most important military events of the American Civil War because it opened the Mississippi River, cutting the Confederacy in two. The siege operations in and of themselves have a lot to offer to our understanding of the campaign and the war: the extent of the operations, the complexity of the strategy and tactics, the grueling nature of the day-by-day participation, and the effect on all involved. Only by understanding the siege in vivid detail, in all its complexities, can we fully understand the larger Vicksburg Campaign itself"--